2020
DOI: 10.1177/1555412019897524
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Problem Online Video Gaming and Its Association With Problem Gambling and Suspected Motivational, Mental Health, and Behavioral Risk Factors in a Sample of University Students

Abstract: Recently, the issue of problem online video game playing and its potential connection with problem gambling has drawn increased attention. Although conceptually similar to many behavioral addictions, there is still no clear consensus on how to best measure and assess problem video game playing. This study validates one proposed measure of problem video gaming—the Problem Video Game Playing Test (PVGT)—in a Canadian undergraduate university student sample. Multivariate results indicate that problem video gaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
12
0
1
Order By: Relevance
“…King and colleagues (2011) examined the links between problem video gaming, as measured through the PVGT (King et al, 2011); problem gambling, as measured by the Problem Gambling Severity Index (PGSI; Currie et al, 2013;Wynne, 2003); and several risk factors thought to be common to both. King and colleagues (2011) reported linkages between each of these factors and the PVGT; however, we published a similar study with a sample of Canadian undergraduate students and found that although there was evidence for a significant connection between these items at the bivariate level, these linkages became insignificant when we controlled for other factors (Biegun et al, 2020). This result is similar to other research results that suggest a lack of direct connection between problem video gaming and problem gambling (Delfabbro et al, 2009).…”
Section: Risk Factors For Problem Gaming and Problem Gamblingsupporting
confidence: 85%
“…King and colleagues (2011) examined the links between problem video gaming, as measured through the PVGT (King et al, 2011); problem gambling, as measured by the Problem Gambling Severity Index (PGSI; Currie et al, 2013;Wynne, 2003); and several risk factors thought to be common to both. King and colleagues (2011) reported linkages between each of these factors and the PVGT; however, we published a similar study with a sample of Canadian undergraduate students and found that although there was evidence for a significant connection between these items at the bivariate level, these linkages became insignificant when we controlled for other factors (Biegun et al, 2020). This result is similar to other research results that suggest a lack of direct connection between problem video gaming and problem gambling (Delfabbro et al, 2009).…”
Section: Risk Factors For Problem Gaming and Problem Gamblingsupporting
confidence: 85%
“…Concerning the age of the samples, ten studies comprised both adolescent and adult samples (Király et al 2015 (Loton et al 2016;Šporčić and Glavak-Tkalić 2018;Billieux et al 2013Billieux et al , 2015Kim et al 2016;Kirby et al 2014), eight studies comprised school students from nine to 19 years old (Milani et al 2018;Schneider et al 2018;Rosenkranz et al 2017;Kwon et al 2011;Dreier et al 2017;Hellström et al 2012Hellström et al , 2015Xu et al 2012), and two studies comprised university students (Biegun et al 2020;Li et al 2016). Eleven studies comprised gamers without specifying the type of videogame played (Milani et al 2018;Loton et al 2016;Schneider et al 2018;von der Heiden et al 2019;Biegun et al 2020;Rosenkranz et al 2017;Kwon et al 2011;Dreier et al 2017;Kim et al 2016;Király et al 2017;Xu et al 2012), five studies comprised World of Warcraft players (Kardefelt-Winther 2014a, b; Billieux et al 2013Billieux et al , 2015Kirby et al 2014), two studies comprised MMORPG players (Kaczmarek and Drążkowski 2014;Dauriat et al 2011), two studies comprised MMOPRG and FPS players (Király et al 2015;Maroney et al 2019), and two studies comprised general gamers and MMORPG players (Hellström et al 2012(Hellström et al , 2015. Samples ...…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…Eleven studies comprised gamers without specifying the type of videogame played (Milani et al 2018;Loton et al 2016;Schneider et al 2018;von der Heiden et al 2019;Biegun et al 2020;Rosenkranz et al 2017;Kwon et al 2011;Dreier et al 2017;Kim et al 2016;Király et al 2017;Xu et al 2012), five studies comprised World of Warcraft players (Kardefelt-Winther 2014a, b; Billieux et al 2013Billieux et al , 2015Kirby et al 2014), two studies comprised MMORPG players (Kaczmarek and Drążkowski 2014;Dauriat et al 2011), two studies comprised MMOPRG and FPS players (Király et al 2015;Maroney et al 2019), and two studies comprised general gamers and MMORPG players (Hellström et al 2012(Hellström et al , 2015. Samples of the four remaining studies comprised recreational and esport gamers (Bányai et al 2019), FPS, role-playing, adventures, MOBA and MMORPG players (Šporčić and Glavak-Tkalić 2018), addicted and non-addicted general online gamers (Li et al 2016 Kirby et al 2014) and ten collected data offline (Schneider et al 2018;Milani et al 2018;Li et al 2016;Biegun et al 2020;Rosenkranz et al 2017;Dreier et al 2017;Kwon et al 2011;Hellström et al 2012Hellström et al , 2015Xu et al 2012).…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the current social science study related to games is mainly focused on such direction, including but not limited to game addiction, player identity, game strategy and game development, e-sport, etc. Among those, game addiction is the most popular topic, and more novel research cases such as the influence of gambling psychology in games on players [7]. The majority of existing articles attempted to demonstrate the addiction effects of games.…”
Section: Literature Reviewmentioning
confidence: 99%